Research Review: Cognitive bias modification of interpretations in youth and its effect on anxiety: a meta‐analysis. (20th October 2017) - Krebs, Georgina; Pile, Victoria; Grant, Sean; Degli Esposti, Michelle; Montgomery, Paul; Lau, Jennifer Y.F.
Abstract : Background: Emerging evidence suggests that cognitive bias modification of interpretations (CBM‐I) is effective in altering interpretation biases and reducing anxiety in adults. Less is known about the impact of CBM‐I in young people, but some recent findings, including a meta‐analysis of combined cognitive bias modification of interpretation and attention techniques, have cast doubt on its clinical utility. Given the current debate, this meta‐analysis sought to establish the independent effects of CBM‐I on interpretations biases and anxiety in youth. Methods: Studies were identified through a systematic literature search of PsycINFO, Ovid MEDLINE, PsycARTICLES, Web of Science and EMBASE between January 1992 and March 2017. Eligible studies aimed to target interpretation biases; did not combine CBM‐I with another intervention; included a control condition; randomly allocated participants to conditions; assessed interpretation bias and/or anxiety as an outcome; included individuals up to age 18; and did not present previously reported data. Reference lists of included articles were checked for further eligible studies, and authors were contacted for unpublished data. Results: We identified 26 studies meeting eligibility criteria that included in the meta‐analysis. CBM‐I had moderate effects on negative and positive interpretations ( g  =   −0.70 and g  =   −0.52, respectively) and a small but significant effect on anxiety assessed after training ( g  =   −0.17) and after a stressor ( g  =   −0.34). No significant moderators were identified. Conclusions: In contrast to previous meta‐analytic findings, our results indicate that CBM‐I has potential but weak anxiolytic effects in youth. Our findings suggest that it may be premature to disregard the potential value of CBM‐I research and further research in this field is warranted.